ผลกระทบจากพระราชบัญญัติวิธีพิจารณาคดีผู้บริโภค พ.ศ. 2551 ต่อผู้ประกอบธุรกิจประเภทสินค้า - โกศล อัศวเดชานุกร (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
Consumer Case Procedure Act B.E. 2551 was enacted in order to provide the speedy remedy to the consumer at a lower legal action expenses. Nevertheless, in views of the business operators, there have been various concerns to the enforcement of this Act in that some legal issues regarding in particular the restrictions imposed upon the business operators remain rather confusing. This thesis focus on the impacts of such law towards the businesses relating to electronic, electric products, and automobiles, and then compares this Act with the consumer protection under the existing civil procedure, and the US laws which has continual development on the consumer protection law. It appears from this study that this act does not provide any negative effect upon the business operators. Instead, the business operators also benefit from the continual proceeding in the same manner as the consumer does whereas these attributes has never existed in the civil procedure. In the US, although there is no specific law on consumer case procedure but the civil procedure and particularly the class action will prevent the business operators from the repeating trials, and thereby creates the unity in the court rulings. It is found that the class action, if imported to Thai legal procedure, will be of significant benefit. This thesis also demonstrates in detail the issue concerning the burden of proof which is regarded another core value of this act in order that the good faith business operators will be able to prepare the information relating to the production process, and the document manifesting the quality of the goods to knock out the allegation that the consumer suffers damage from such goods.